Test–retest repeatability and reproducibility of ADC measures by breast DWI: Results from the ACRIN 6698 trial. Issue 6 (22nd October 2018) - Newitt, David C.; Zhang, Zheng; Gibbs, Jessica E.; Partridge, Savannah C.; Chenevert, Thomas L.; Rosen, Mark A.; Bolan, Patrick J.; Marques, Helga S.; Aliu, Sheye; Li, Wen; Cimino, Lisa; Joe, Bonnie N.; et al.
Abstract : Background: Quantitative diffusion‐weighted imaging (DWI) MRI is a promising technique for cancer characterization and treatment monitoring. Knowledge of the reproducibility of DWI metrics in breast tumors is necessary to apply DWI as a clinical biomarker. Purpose: To evaluate the repeatability and reproducibility of breast tumor apparent diffusion coefficient (ADC) in a multi‐institution clinical trial setting, using standardized DWI protocols and quality assurance (QA) procedures. Study Type: Prospective. Subjects: In all, 89 women from nine institutions undergoing neoadjuvant chemotherapy for invasive breast cancer. Field Strength/Sequence: DWI was acquired before and after patient repositioning using a four b‐value, single‐shot echo‐planar sequence at 1.5T or 3.0T. Assessment: A QA procedure by trained operators assessed artifacts, fat suppression, and signal‐to‐noise ratio, and determine study analyzability. Mean tumor ADC was measured via manual segmentation of the multislice tumor region referencing DWI and contrast‐enhanced images. Twenty cases were evaluated multiple times to assess intra‐ and interoperator variability. Segmentation similarity was assessed via the Sørenson–Dice similarity coefficient. Statistical Tests: Repeatability and reproducibility were evaluated using within‐subject coefficient of variation (wCV), intraclass correlation coefficient (ICC), agreement index (AI), and repeatability coefficient (RC). Correlations were measured by Pearson's correlation coefficients. Results: In all, 71 cases (80%) passed QA evaluation: 44 at 1.5T, 27 at 3.0T; 60 pretreatment, 11 after 3 weeks of taxane‐based treatment. ADC repeatability was excellent: wCV = 4.8% (95% confidence interval [CI] 4.0, 5.7%), ICC = 0.97 (95% CI 0.95, 0.98), AI = 0.83 (95% CI 0.76, 0.87), and RC = 0.16 * 10 −3 mm 2 /sec (95% CI 0.13, 0.19). The results were similar across field strengths and timepoint subgroups. Reproducibility was excellent: interreader ICC = 0.92 (95% CI 0.80, 0.97) and intrareader ICC = 0.91 (95% CI 0.78, 0.96). Data Conclusion: Breast tumor ADC can be measured with excellent repeatability and reproducibility in a multi‐institution setting using a standardized protocol and QA procedure. Improvements to DWI image quality could reduce loss of data in clinical trials. Level of Evidence: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;49:1617–1628.